The Falsification of Four Popular Hypotheses about International Financial Behavior during the Asian Crisis - Thomas D. Willett; Aida Budiman; Arthur Denzau; Gab-Je Jo; Cesar Ramos; John Thomas (Claremont McKenna College, Department of Economics, 2001)
Various claims have been made about the causes of the Asian crisis and its spread. Here, we use data on the behavior of capital flows during the crisis to test the strong forms of four such hypotheses, including the dominant role of portfolio investors and hedge funds in initiating and spreading the crisis; moral hazard; and, finally, the role of Japanese banks in spreading the trouble to countries in which they were the largest source of funds. All are falsified as monocausal explanations. For example, portfolio investments that could not have been subject to substantial moral hazard continued to flow into Asia until very shortly before the crisis. Likewise, contrary to common expectations banks were a much larger source of capital outflows during the crisis than were portfolio investors. While falsified in their strongest forms, several of these hypotheses in less strong form should play a role in a more nuanced analysis. It is time to move past simple single-factor approaches in order to produce a more complete, synthetic explanation of this episode.
Keywords: 330